Sinus Development and Pneumatization in a Primary Ciliary Dyskinesia Cohort. Issue 1 (January 2021) - Pappa, Andrew K.; Sullivan, Kelli M.; Lopez, Erin M.; Adams, Katherine N.; Zanation, Adam M.; Ebert, Charles S.; Thorp, Brian D.; Senior, Brent A.; Leigh, Margaret W.; Knowles, Mike R.; Kimple, Adam J.
Background: Primary ciliary dyskinesia (PCD) is a genetically diverse disease which causes impaired mucociliary clearance, and results in pulmonary, otologic, and rhinologic disease in affected patients. Genetic mutations in multiple genes impair the ability of patients to clear mucous from the lungs, middle ear, and sinonasal cavity and lead to chronic pulmonary and sinonasal symptoms. Methods: We identified 17 PCD patients who had available CT scans. Volumes for bilateral maxillary, sphenoid, and frontal sinuses were calculated. A control population of patients who had preoperative CT scans for endoscopic endonasal resection of skull base pathology without sinonasal cavity involvement was also identified. Results: The mean age of PCD was 33 and ranged from 13 to 54 years. Patients were age- and gender-matched to a control group that underwent resection of anterior skull-base tumors and had a mean age of 35 that ranged between 17–53 years old. The volumes for all thee sinus cavities were significantly smaller (p < 0.007) compared to the control population. The average Lund-Mackay score was 10.6 in the PCD cohort (range 6–16) in comparison to an average of 0.7 in the control cohort (range 0–2). Conclusions: Overall sinus volumes were smaller in patients with PCD compared to our control population. Future studies will be aimed at understanding defects in sinus development as a function of specific genetic mutations in PCD patients. Ultimately, a better understanding of the underlying pathophysiology of PCD will allow us to identify the optimal treatment practices for this unique patient group.